Scenario modules, ray‐tracing simulations and analysis of millimetre wave and terahertz channels for smart rail mobility. Issue 4 (21st February 2018) - Guan, Ke; Ai, Bo; Peng, Bile; He, Danping; Lin, Xue; Wang, Longhe; Zhong, Zhangdui; Kürner, Thomas
Abstract : Millimeter wave (mmWave) and Terahertz (THz) technologies are the enabler of providing high‐data rate communications for 'smart rail mobility'. In this paper, six scenario modules for mmWave and THz train‐to‐infrastructure channels are defined and constructed. All the main objects, such as tracks, stations, crossing bridges, tunnels, cuttings, barriers, pylons, buildings, vegetation, traffic signs, billboards, trains, etc., are modeled according to the typical geometries and materials in reality. The three‐dimensional (3D) models of these six modules are publicly available and freely downloadable. Furthermore, extensive ray‐tracing simulations in the 60 GHz band with 8 GHz bandwidth are made in all the six modules with two antenna setups. Path loss exponent, shadow factor, Ricean K ‐factor, root‐mean‐square (RMS) delay spread, and coherence bandwidth are extracted and analyzed. These channel characteristics show that the objects that might not be so impacting on lower frequency channels indeed influence mmWave channel properties, and therefore, they can even play a more important role in the channels at higher frequency bands – THz. The channel characteristics analyzed in this study provide the foundation for future work that aims to streamline the design, simulation, and development of mmWave and THz communications enabling smart rail mobility.